Curriculum Transformation in The 21st Century Education: Perspectives, Challenges, and Prospects - Dariyono, D; Rusman, R (Proceedings International Conference on Education Innovation and Social Science, 2023)
Massive changes in various aspects of life are characteristic of the 21st century, triggered by the rapid development of technology. In facing this era of technological progress, globalization and social complexity, education must adapt its curriculum so that students are equipped with skills and competencies that are relevant to the ever-changing demands of the global market. Innovation in the curriculum is a must, which not only addresses current problems but also integrates 21st century skills. This article aims to examine the competencies required by 21st century education and identify the challenges faced in implementing curriculum changes. This study uses a literature review methodology, taking sources from textbooks, scientific journals, and the latest research findings. The selected sources meet the criteria of relevance and novelty. 21st century skills needed to carry out curriculum transformation include critical thinking, creativity, collaboration, communication, digital literacy, and problem solving. Challenges in implementing curriculum changes that need attention include intensive teacher training, development of appropriate assessments, support from various parties, and adequate resource allocation. Overall, curriculum transformation can create relevant, contextual, and responsive learning experiences that meet student needs in an ever-changing educational landscape.